Pengaruh Leverage dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Industri Dasar dan Kimia - Aditya, Ilham; Hasanah, Nuramalia; Mardi; Armeliza, Diah (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2021)
Firm value can be influenced by various factors, namely leverage, firm size and profitability. In addition, profitability in this study acts as a variable that mediates leverage and firm size on firm value. The purpose of this study was to determine the effect of leverage and firm size on firm value with profitability as an intervening variable. The unit of analysis is the basic and chemical industry companies listed on the IDX 2016-2019. The research method used is non-participant observation method. The research population is 60 companies. The sample is 31 companies with a total of 124 sample data with purposive sampling as a sampling technique. Data analysis using path analysis and using SPSS 25 application. Based on the results of the study, it was obtained that leverage, firm size, profitability had a significant positive effect on firm value. Leverage has a significant negative effect on profitability. Firm size has a significant positive effect on profitability. Profitability is able to mediate the relationship between leverage and firm value, but profitability is not able to mediate the relationship between firm size and firm value.